Effect of Low‐Furanocoumarin Hybrid Grapefruit Juice Consumption on Midazolam Pharmacokinetics. (6th September 2016) - Kawaguchi‐Suzuki, Marina; Nasiri‐Kenari, Negar; Shuster, Jonathan; Gmitter Jr., Fred G.; Cancalon, Paul; de Oliveria, Felipe; Kight, Jennifer; Handberg, Eileen M.; Pepine, Carl J.; Frye, Reginald F.; Cooper‐DeHoff, Rhonda M.
Abstract: The objectives of this study were to investigate the effect of grapefruit juice low in furanocoumarins on CYP3A activity and to summarize previous findings of enzyme inhibition measured by the metabolism of midazolam after intake of grapefruit juice. Twelve healthy volunteers participated in a prospective, randomized, double‐blinded, 3‐way crossover clinical study to determine the effect of regular grapefruit juice (RGJ) and a novel, low‐furanocoumarin hybrid grapefruit juice (HGJ) on the metabolism of oral midazolam, used as a probe for in vivo CYP3A activity, compared with water as a control. The RGJ was 100% hand‐squeezed "Hudson" grapefruit juice, and the HGJ contained low amounts of furanocoumarin constituents. The point estimates (90% confidence intervals) for the RGJ/water midazolam AUC geometric mean ratio was 122% (107‐140). The point estimate for the HGJ/water midazolam AUC ratio was within the 80% to 125% bioequivalence range, indicating an absence of interaction. This finding also prompted a systematic review of available evidence on the pharmacokinetic alteration of midazolam by grapefruit juice. Although most studies demonstrated alteration in midazolam pharmacokinetics supporting inhibition of CYP3A activity as a likely mechanism, the cohorts included in these studies and the extent of the pharmacokinetic interaction varied widely. The current study indicated grapefruit juice‐drug interaction varies substantially based on patient characteristics and/or grapefruit juice product‐related factors, including the amount of furanocoumarin constituents present in the juice.